SISTEMA DE EJERCICIOS PARA EL DESARROLLO DE LA MOTRICIDAD GRUESA DE LOS NIÑOS EN EDAD DE 11 AÑOS DE LA UNIDAD EDUCATIVA "MARÍA DE SAN JOSÉ" - SOLEDISPA RODRIGUEZ ARIEL ALEJANDRO (2024)
This research project aims to develop a system of exercises for the development of gross motor skills in children aged 11 years from the "María de San José" Educational Unit, Simón Bolívar canton. The researchers, according to the diagnosis made, were able to observe the delays in the gross motor development of the students, with them they realized the deficiencies in the muscle groups that control the largest movements of the entire body and the delay in involving hands, arms, legs and trunk in some primary exercises. The methodology used was a descriptive and quantitative field investigation with its field test instrument because the institution was visited to analyze, observe and evaluate the sample of selected students. Then, analyzing the problem, it is necessary to implement a system of evaluation. exercises for students to improve their motor skills, and also recommend to the school that from the initial courses they carry out activities that complement motor development. Children from the first years of life should exercise according to their age so that in the future they do not have problems with the coordination of their body in performing a number of exercises and with this they advance both in age and in fine and gross motor skills.